2020
DOI: 10.1155/2020/6679846
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial R&D Resource Allocation Efficiency Based on VR Technology and Machine Learning in Complex Systems on Total Factor Productivity

Abstract: With the development of the globalization of science and technology, innovation has become an important driving force for regional economic development. As a core element of regional innovation, financial R&D resources have also become a key element to enhance national innovation capabilities and national economic competitiveness. National and regional innovation capabilities have a direct impact. There are also many deep-seated problems behind the world-renowned achievements, such as irrational industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Through the theoretical analysis in Section 2, it can be found that the synergistic governance effect of carbon trading policy and public environmental supervision enhances the ESG performance of firms by influencing their R&D and innovation investment, resource allocation efficiency, and sustainability awareness. In order to test whether this view is valid at the micro enterprise level in reality, referring to Sun and Zhong (2020), Wang R. et al (2022), andLi et al (2023), this paper uses firms' R&D investment intensity (RDI), total factor productivity (TFP), and executives' awareness of sustainable development (EAS) to measure firms' R&D and innovation investment, resource allocation efficiency, and sustainable development awareness, respectively. The mechanism test model is set up as follows:…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Through the theoretical analysis in Section 2, it can be found that the synergistic governance effect of carbon trading policy and public environmental supervision enhances the ESG performance of firms by influencing their R&D and innovation investment, resource allocation efficiency, and sustainability awareness. In order to test whether this view is valid at the micro enterprise level in reality, referring to Sun and Zhong (2020), Wang R. et al (2022), andLi et al (2023), this paper uses firms' R&D investment intensity (RDI), total factor productivity (TFP), and executives' awareness of sustainable development (EAS) to measure firms' R&D and innovation investment, resource allocation efficiency, and sustainable development awareness, respectively. The mechanism test model is set up as follows:…”
Section: Mechanism Analysismentioning
confidence: 99%